2016
DOI: 10.1093/nutrit/nuw045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diet on mortality and cancer recurrence among cancer survivors: a systematic review and meta-analysis of cohort studies

Abstract: Context: Evidence of an association between dietary patterns and individual foods and the risk of overall mortality among cancer survivors has not been reviewed systematically. Objective: The aim of this meta-analysis of cohort studies was to investigate the association between food intake and dietary patterns and overall mortality among cancer survivors. Data Sources: The PubMed and Embase databases were searched. Study Selection: A total of 117 studies enrolling 209 597 cancer survivors were included. Data E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
206
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 216 publications
(234 citation statements)
references
References 56 publications
10
206
0
7
Order By: Relevance
“…In breast cancer survivors (41 cohort studies), a recently published systematic review and meta-analysis [26] showed an association of decreased overall mortality and adherence to high diet quality indices (high intake of fruit, vegetables, whole grains, legumes, and nuts as well as low intake of red and processed meat) (RR 0.74, 95% CI 0.60-0.90, 3 studies) and adherence to a prudent/healthy dietary pattern (high intake of fruit, vegetables, whole grains, poultry, and low-fat dairy products) (RR 0.76, 95% CI 0.60-0.95, 3 studies). High adherence to a Western/unhealthy dietary pattern (high intake of red and processed meat, refined grains, sweets and desserts, and high-fat dairy products) was associated with an increased risk of overall mortality (RR 1.44, 95% CI 1.17-1.77, 3 studies) [26].…”
Section: Role Of Dietary Patternsmentioning
confidence: 99%
See 3 more Smart Citations
“…In breast cancer survivors (41 cohort studies), a recently published systematic review and meta-analysis [26] showed an association of decreased overall mortality and adherence to high diet quality indices (high intake of fruit, vegetables, whole grains, legumes, and nuts as well as low intake of red and processed meat) (RR 0.74, 95% CI 0.60-0.90, 3 studies) and adherence to a prudent/healthy dietary pattern (high intake of fruit, vegetables, whole grains, poultry, and low-fat dairy products) (RR 0.76, 95% CI 0.60-0.95, 3 studies). High adherence to a Western/unhealthy dietary pattern (high intake of red and processed meat, refined grains, sweets and desserts, and high-fat dairy products) was associated with an increased risk of overall mortality (RR 1.44, 95% CI 1.17-1.77, 3 studies) [26].…”
Section: Role Of Dietary Patternsmentioning
confidence: 99%
“…High adherence to a Western/unhealthy dietary pattern (high intake of red and processed meat, refined grains, sweets and desserts, and high-fat dairy products) was associated with an increased risk of overall mortality (RR 1.44, 95% CI 1.17-1.77, 3 studies) [26]. No association was found with single food groups, and no significant results were presented for recurrence or breast cancer-specific mortality [26].…”
Section: Role Of Dietary Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent systematic review and meta‐analysis summarized evidence on dietary factors and risk of CRC and indicated that higher intake of red and processed meat was associated with increased risk of CRC, while higher intake of whole grains, dairy products, vegetable and fish showed inverse associations with risk . Previous meta‐analyses pointed out that dietary patterns were also related to risk of CRC, and mortality among CRC survivors . A “healthy” dietary pattern, characterized by high intake of vegetables, fruit, whole grains, olive oil, fish, soy, poultry and low‐fat dairy was associated with decreased risk of CRC, whereas a “western” diet, characterized by high consumption of red and/or processed meat, refined grains, sweets, high‐fat dairy products, butter, potatoes and high‐fat gravy and low intake of fruit and vegetables was related to increased risk of CRC .…”
Section: Introductionmentioning
confidence: 99%